STRENGHTENING THE ROLE OF THE GENERAL ASSEMBLY IN APPOINTMENT OF THE SECRETARY GENERAL- NECESSITIES AND POSSIBILITIES - Gordanic, Jelica (Zbornik radova Pravnog fakulteta u Novom Sadu, 2020)
The Secretary-General is appointed by the General Assembly upon the recommendation of the Security Council. Due to the veto power of the permanent members, lack of transparency and the recommendation of only one candidate, the appointment of the Secretary-General is basically a decision of the Security Council. UN member states, civil society organizations and theorists point out the need for a more active role of the General Assembly during the appointment of the Secretary-General. Formation of the ad hoc working group for the revitalization of the work of the General Assembly raised this problem to a higher level. Current procedure of appointment of the Secretary-General had sense at the time of the adoption of the UN Charter. The circumstances of the 21st century require different solutions. The paper aims to show the necessity and possibilities of strengthening the role of the General Assembly in the process of appointment of the Secretary-General and obstacles existing in this regard. The long-term activities of the ad hoc working group for the revitalization of the work of the General Assembly gave positive results in terms of more active role of the General Assembly during the appointment of the Secretary General in 2016. The paper aims to show that the results achieved by the ad hoc working group are not long-term efficient. The most effective solution for strengthening the role of the General Assembly in the appointment of the Secretary-General is the revision of the UN Charter.